Foundations of organic chemistry : unity and diversity of structures, pathways, and reactions - Dalton, David R., 1936- (Hoboken, NJ : Wiley, 2020)
'This book differs from other organic chemistry textbooks in that it is directed to all students studying organic chemistry rather than students studying for entry to professional school. It directs the reader to question assumptions rather than to accept what is told. As a consequence, the work is heavily referenced to the original literature of organic chemistry so that the interested students can delve into early thinking about processes and to ask'How and why was that done?' and to explain how what is held as rudimentary or foundational came to be so. In this edition, the author adds discussion of genetic tools like CRISPR and of metal organic frameworks (MOF's) for storage of fuels, capture of carbon dioxide, and catalytic applications. The author has also developed a solutions guide for adopting instructors to access via a companion website'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Chemistry, Organic -- Textbooks